2015
DOI: 10.3727/096368915x686887
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Delivery of Bone Marrow Mesenchymal Stem Cells Improved Neurovascular Regeneration and Rescued Neuropsychiatric Deficits after Neonatal Stroke in Rats

Abstract: Neonatal stroke is a major cause of mortality and long-term morbidity in infants and children. Currently, very limited therapeutic strategies are available to protect the developing brain against ischemic damage and promote brain repairs for pediatric patients. Moreover, children who experienced neonatal stroke often have developmental social behavior problems. Cellular therapy using bone marrow mesenchymal stem cells (BMSCs) has emerged as a regenerative therapy after stroke. In the present investigation, neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 69 publications
(83 reference statements)
0
63
0
Order By: Relevance
“…HP-BMSC-treated mice performed much better than N-BMSC- and vehicle-treated animals (Wei et al , 2013). Furthermore, we demonstrated in a neonatal stroke model of rats that intranasally delivered BMSCs showed beneficial effects on brain development after stroke and that rat pups receiving HP-BMSCs developed better sensorimotor activity, olfactory functional recovery, and performed better in social behavioral tests (Wei et al , 2015). Recently, we showed that intranasal delivery of HP-BMSCs enhanced neurogenesis and angiogenesis after intracerebral hemorrhagic stroke in mice (Sun et al , 2015).…”
Section: Stem Cell/neural Progenitor Transplantation In Animal Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…HP-BMSC-treated mice performed much better than N-BMSC- and vehicle-treated animals (Wei et al , 2013). Furthermore, we demonstrated in a neonatal stroke model of rats that intranasally delivered BMSCs showed beneficial effects on brain development after stroke and that rat pups receiving HP-BMSCs developed better sensorimotor activity, olfactory functional recovery, and performed better in social behavioral tests (Wei et al , 2015). Recently, we showed that intranasal delivery of HP-BMSCs enhanced neurogenesis and angiogenesis after intracerebral hemorrhagic stroke in mice (Sun et al , 2015).…”
Section: Stem Cell/neural Progenitor Transplantation In Animal Modelsmentioning
confidence: 99%
“…4). The pro-survival and an enhanced homing to the ischemic brain were later demonstrated using BMSCs (Theus et al , 2008b; Wei et al , 2012; Wei et al , 2015; Yu et al , 2013). …”
Section: Strategies To Enhance Cell Survival After Transplantation: Gmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, MSCs have enjoyed the most interest as therapeutic vectors. MSCs are stromal cells that can be isolated from bone marrow and human cord blood, which are able to differentiate along a variety of mesodermal lineages (Pittenger et al, 1999), and have been proposed as potential therapeutic agents for a wide variety of neural disorders, including neonatal brain injury (Donega et al, 2014; Wei et al, 2015), ischemic stroke (Gutierrez-Fernandez et al, 2013), and the neurodegenerative disorders (Castorina et al, 2015), as well as multiple sclerosis and the inflammatory myelin disorders (Ben-Hur and Goldman, 2008; Einstein and Ben-Hur, 2008). They are not, however, vectors for cell replacement, in that little credible evidence has yet supported the notion that genetically-unmodified MSCs might differentiate along neuroepithelial lineages.…”
Section: Cellular Phenotypes Appropriate For Treatment Of the Myelin mentioning
confidence: 99%